a. -32 / (-24 / (=3)] = 4
b. -48 / 16 - (-5) = 2
6. -6 x 12 / (-9) = 8
d. -7 + (-42) / 7 = -13
e. [-59 - (-17)] / (-6) = 7
Step-by-step explanation:
We need to evaluate each expression:
a. -32 / (-24 / (=3)]
⇒ [tex]\frac{-32}{\frac{-24}{3}}[/tex]
⇒ [tex]\frac{-32}{-24}(3)[/tex]
⇒ [tex]\frac{32}{8}[/tex]
⇒ [tex]4[/tex]
b. -48 / 16 - (-5)
⇒ [tex]\frac{-48}{16} - (-5)[/tex]
⇒ [tex]-3 +5[/tex]
⇒ [tex]2[/tex]
6. -6 x 12 / (-9)
⇒ [tex]\frac{-6(12)}{-9}[/tex]
⇒ [tex]\frac{-2(12)}{-3} = 2(4)[/tex]
⇒ [tex]8[/tex]
d. -7 + (-42) / 7
⇒ [tex]-7+\frac{-42}{7}[/tex]
⇒ [tex]-7-6[/tex]
⇒ [tex]-13[/tex]
e. [-59 - (-17)] / (-6)
⇒ [tex]\frac{-59-(-17)}{-6}[/tex]
⇒ [tex]\frac{-42}{-6}[/tex]
⇒ [tex]7[/tex]